2024 European Heart Rhythm Association/Heart Rhythm Society/Asia Pacific Heart Rhythm Society/Latin American Heart Rhythm Society expert consensus statement on catheter and surgical ablation of atrial fibrillation - Stylianos Tzeis; Edward P. Gerstenfeld; Jonathan Kalman; Eduardo B. Saad; Alireza Sepehri Shamloo; Jason G. Andrade; Chirag R. Barbhaiya; Tina Baykaner; Serge Boveda; Hugh Calkins; Ngai‐Yin Chan; Minglong Chen; et al. (Journal of Arrhythmia)
Abstract In the last three decades, ablation of atrial fibrillation (AF) has become an evidence‐based safe and efficacious treatment for managing the most common cardiac arrhythmia. In 2007, the first joint expert consensus document was issued, guiding healthcare professionals involved in catheter or surgical AF ablation. Mounting research evidence and technological advances have resulted in a rapidly changing landscape in the field of catheter and surgical AF ablation, thus stressing the need for regularly updated versions of this partnership which were issued in 2012 and 2017. Seven years after the last consensus, an updated document was considered necessary to define a contemporary framework for selection and management of patients considered for or undergoing catheter or surgical AF ablation. This consensus is a joint effort from collaborating cardiac electrophysiology societies, namely the European Heart Rhythm Association, the Heart Rhythm Society, the Asia Pacific Heart Rhythm Society, and the Latin American Heart Rhythm Society